2003
DOI: 10.1248/jhs.49.429
|View full text |Cite
|
Sign up to set email alerts
|

Use of Paramecium Species in Bioassays for Environmental Risk Management: Determination of IC50 Values for Water Pollutants

Abstract: Effect of chemical water pollutants on the growth of two Paramecium species (Paramecium caudatum and Paramecium trichium) were examined. The chemicals used as model chemical pollutants include organic solvents, potential carcinogens, mutagens, metabolic modulators, herbicides, insecticides, fungicides, antimicrobials, heavy metals, and heavy metal-containing chemicals. In this study, the IC 50 values indicating the concentration of substances inhibiting the proliferation of Paramecium cells by 50% were used in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 14 publications
(17 reference statements)
1
19
1
Order By: Relevance
“…Further, no significant impacts on the protozoa or micrometazoa numbers were found when the community developed in the presence of 10 g l −1 TCS. Miyoshi et al (2003) however, reported that TCS was toxic to Paramecium trichium and Paramecium caudatum at concentrations of 2.58 M (about 750 g l −1 ) and 1.64 M (about 476 g l −1 ), respectively. In the current study there were clear negative effects on protozoan grazers relative to the reference community.…”
Section: Response Of the Protozoa/micrometazoamentioning
confidence: 97%
“…Further, no significant impacts on the protozoa or micrometazoa numbers were found when the community developed in the presence of 10 g l −1 TCS. Miyoshi et al (2003) however, reported that TCS was toxic to Paramecium trichium and Paramecium caudatum at concentrations of 2.58 M (about 750 g l −1 ) and 1.64 M (about 476 g l −1 ), respectively. In the current study there were clear negative effects on protozoan grazers relative to the reference community.…”
Section: Response Of the Protozoa/micrometazoamentioning
confidence: 97%
“…It belongs to the Ciliate phylum (Ciliophora). The use of Paramecium species as a model of survey has been reported by several authors in some disciplines; in ecotoxicology, Paramecium species were used to study environmental qualities and toxic effects of industrial, agricultural and domestic chemicals (Edmiston et al, 1985;Madoni, 2000;Miyoshi et al, 2003;Takahashi et al, 2005;Venkateswara et al, 2006;Rouabhi et al, 2006;Mortuza et al, 2009Mortuza et al, , 2010Amanchi, 2010); in genetic, because its sequencing genome is well known, researchers used P. tetraurelia for genetic analysis, gene expression and mutation (Houten et al, 1977;Brygoo, 1977;Mayer et al, 1998;Haynes et al, 2000;Vayssié et al, 2000). In physiology, paramecia are used in general for studying the role, the function and the cell organization.…”
Section: Introductionmentioning
confidence: 99%
“…With these advantages, the use of paramecia can permit a quicker and more convenient evaluation of the toxicity of various polluting chemicals. 11) In addition, ciliates are important components of the aquatic food chain 12) and play an essential role in the purification processes of both aerobic and anaerobic biological wastewater treatment systems. 13,14) In spite of the important roles played by the ciliated protozoa in the ecology of freshwater ecosystems, little is known about the accumulation efficiency of heavy metals by ciliates.…”
Section: Paramecium Bursariamentioning
confidence: 99%
“…11,13,14,19,[22][23][24] The study of P. bursaria and its interaction with chromium may be useful for bioremediation of chromium-contaminated environments. The aim of the study was to determine the ability of P. bursaria to accumulate chromium.…”
Section: P Bursariamentioning
confidence: 99%